Religiosity, Economic Stress, and Subjective Well-Being Family of Elderly Farm Workers - Djaya, Reski Amalia Putra; Herawati, Tin; Krisnatuti, Diah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study employed a cross-sectional design and was conducted quantitatively, aiming to analyze the influence of religiosity and economic pressure on the well-being of elderly farm laborer families. The study involved 60 elderly men and 60 elderly women who had worked as farm laborers in the past year, selected through purposive sampling. Based on the results, the average age of elderly male and female farm laborers was 67 years. Elderly male farm laborers had higher educational attainment and a greater number of family members compared to elderly female farm laborers. More than half of the elderly male farm laborers had spouses and worked as permanent laborers, whereas the female farm laborers were mostly widowed and worked as daily laborers. The majority of both elderly male and female farm laborers had per capita incomes below the poverty line. Religiosity levels in both groups were categorized as high. Objective and subjective economic pressures in both groups ranged from low to moderate. The subjective well-being of both groups was categorized as moderate. Religiosity, and subjective economic pressure had both positive and negative significant influences on the subjective well-being of elderly farm laborers.